PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KEPUASAN DAN KINERJA KARYAWAN PT. PEPUTRA SUPRA JAYA PEKANBARU - Indarti, Sri (Jurnal Tepak Manajemen Bisnis, 2015)
The purpose of this study was to determine the magnitude seen effect of motivation and discipline of work satisfaction and performance PT. Supra Peputra Jaya Pekanbaru. As for the object of the object of study is the employees at PT. Supra Peputra Jaya Pekanbaru.In this study,the population is population is PT. Supra Peputra Jaya Pekanbaru totaling 173 people, while the sample amounted to 63 employees. The data collected in the form of quantitative data and qualitative consist of primary data and secondary data. Primary data were obtained from employees of PT. Supra Peputra Jaya Pekanbaru through observation and questionnaires.To find out how much discipline and motivation on employee satisfaction with performance. So the way I did it was by using descriptive method that the entire result of the study could be linked to the theories contained in the theoretical description. To find out what are the factors that affect the performance of employees, it can be done by using a two-stage regression.Based on the research results and calculations indicate that motivation has an influence on satisfaction by 0.284 or 28.4%, and the discipline has an influence on the satisfaction of 0.355 or 35.5%, while satisfaction has an influence on the performance of employees is 0.215 or 21.5% in PT. Supra Peputra Jaya Pekanbaru.Keywords : Motivation, Discipline, Employee Satisfaction and Performance.